Pengembangan Media Pembelajaran Augmented Reality (AR) Terintegrasi Pembelajaran STEM - Halimatus Sakdiah; Riza Andriani; Fajrul Wahdi Ginting; Nuraini Fatmi (Postgraduate, University of Mataram, 2023)
This research is motivated by the development of science and technology in the 21st century, especially in the fields of Augmented Reality (AR) and STEM (Science, Technology, Engineering, and Mathematics) learning which provides opportunities for students to develop work skills and mathematical abilities which lead to the formation of life competencies in the future that is the competence of Education for Sustainable Development Goals (ESDG). This AR Learning Media was developed with a 4D development design: Define, Design, Development, and Dissemination. The subjects of this research were 7th-grade science students and teachers at SMPN 1 Dewantara. Media and content validation was carried out by 2 material experts and a media expert. Instruments used Media validation sheets, materials, and student and teacher response questionnaires. Analysis was done using percentage techniques on validation sheets, teacher response questionnaires, and student responses. The results of this research are AR media prototypes that are very feasible according to material experts and appropriate according to media experts with excellent student responses and the teacher's response was very practical